Kinetic study on the extraction of ethanimidic acid from hibiscus flowers using microwave assisted hydrodistillation - Hesham Hussein Rassem; Mohd Hairul Bin Khamidun; Ahmer Ali Siyal; Radin Maya Saphira Radin Mohamed (Scientific Reports)
Abstract Microwave extraction of active compounds from plants offers an efficient alternative to traditional methods, highlighting the need to investigate its modeling and kinetic mechanisms for comprehensive understanding. This study evaluated kinetic models for the microwave-assisted hydrodistillation (MAHD) of ethanimidic acid from hibiscus flowers. Experimental data, including ethanimidic acid concentration as a function of time, power, and solid-to-liquid ratio, were analyzed using three-parameter empirical models. The second-order model demonstrated superior accuracy (R² = 0.954), outperforming the first-order model, and effectively described the two-stage extraction process: washing and diffusion. The second-order kinetic model ensures precise control of ethanimidic acid extraction, enabling efficient scalability for industrial production and consistent quality for pharmacological applications, emphasizing sustainable and cost-effective manufacturing practices. This model provides a robust framework for advancing MAHD applications in the industrial production of bioactive compounds, promoting innovation in sustainable technologies, and enhancing the economic feasibility of bioactive compound recovery.